Analysing the concept of margin of appreciation in Article 12 of the European Convention on Human Rights regarding same-sex marriages - Kuzņecova, Annija (Riga Graduate School of Law, 2023)
The purpose of this thesis is to identify whether the Margin of Appreciation regarding Article 12 of the European Convention on Human Rights is becoming narrower. This thesis starts by delving into the European Convention on Human Rights history and examining the legislative development of the Margin of Appreciation together with the European Courts of Human Rights. Afterward comes a historical overview of Latvia’s and Netherlands’ legal developments around same-sex marriage and same-sex partnerships. Next, this thesis focuses on analyzing the case law of the European Court of Human Rights regarding same-sex marriages to answer the research question in the final part of the thesis. The research found that, as of now, the application of the Margin of Appreciation is not narrowing, mainly due to the lack of a European consensus regarding this issue.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Human rights law; European Convention on Human Rights; Same-sex marriage; Article 12 of the European Convention on Human Rights